2021
DOI: 10.1177/23259671211010826
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Pediatric Sports Injury Presentation During the COVID-19 Pandemic: A Multicenter Analysis

Abstract: Background: The current coronavirus 2019 (COVID-19) pandemic has prompted a multitude of public health response measures including social distancing, school cancellations, and cessation of organized sports. Purpose: To examine the impact of COVID-19 and corresponding public health measures on the characteristics of common pediatric musculoskeletal injuries associated with sports. Study Design: Cohort study; Level of evidence, 3. Methods: This was a multicenter retrospective cohort study comparing patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 26 publications
1
18
1
Order By: Relevance
“…We are not able to explain the reason for this increase in knee pain prevalence among children, but this trend is similar to the result of a cross-sectional study that reported more musculoskeletal pain due to lifestyle changes among survivors of natural disasters [ 10 ]. Regarding musculoskeletal problems related to the COVID-19 pandemic, a cohort study in the USA showed a significant decrease in pediatric musculoskeletal injuries associated with sports [ 16 ]. Another cross-sectional study showed that 40% of participants with no previous back pain developed back pain during the COVID-19 pandemic [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…We are not able to explain the reason for this increase in knee pain prevalence among children, but this trend is similar to the result of a cross-sectional study that reported more musculoskeletal pain due to lifestyle changes among survivors of natural disasters [ 10 ]. Regarding musculoskeletal problems related to the COVID-19 pandemic, a cohort study in the USA showed a significant decrease in pediatric musculoskeletal injuries associated with sports [ 16 ]. Another cross-sectional study showed that 40% of participants with no previous back pain developed back pain during the COVID-19 pandemic [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many patients and families deferred non-urgent imaging during the lockdown. Moreover, lockdown, home-schooling and suspension of group sports further reduced paediatric cases from sporting injuries[ 39 ]. We did observe a slight increase in some services, such as MRI, during 2020 despite COVID-19 disruption, as services returned to pre-COVID-19 demand.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies published in the literature analyzed the effects of COVID-19 on injuries and procedures during the initial months of the pandemic. A multicenter cohort study examined presentations of pediatric sports injuries, including meniscal and anterior cruciate ligament injury and patella dislocation, during the early (March to May 2020) and mid-pandemic (May to July 2020) period [ 17 ]. Within the first month of the pandemic, significant decreases in injuries were seen compared to pre-pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, no delay in care was observed for these injuries that occurred during the pandemic. Compared to pre-pandemic, more injuries occurred at home due to a decrease in organized sports and most occurred while playing basketball and soccer, which are easily played at home [ 17 ]. Interestingly, the lack of sports participation during the pandemic may result in increased injury rates upon return to play, as suggested by a German elite soccer league that experienced a three-fold increase in injury rates following the COVID-19 lockdown [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation